The Influence of Culture and Job Satisfaction on Organizational Commitment At PT. Bina Administrasi Bandung - Muhammad Taufik; Syamsu Rijal (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
This study will examine and analyse these elements to have a better understanding of how employee culture and job satisfaction impact organisational commitment. This essay's research focuses on the Bandung, Indonesia, PT.Bina Administrasi. The sample for the study was composed of 98 participants using a purposive sampling method. The analysis technique is called multiple regression. Following are the study's conclusions: (1) Organisational culture positively affects organisational commitment, meaning that the better the culture, the higher the commitment. (2) A favourable association between the two can be shown when organisational commitment is high and work satisfaction is high.